2022
DOI: 10.1021/jasms.2c00110
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of MALDI-TOF MS Proteomics and Species-Unique Biomarkers’ Discovery for Rapid Screening of Brucellosis

Abstract: Brucellosis is considered to be a zoonotic infection with a predominant incidence in most parts of Iran that may even simply involve diagnostic laboratory personnel. In the present study, we apply matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) for rapid and reliable discrimination of Brucella abortus and Brucella melitensis, based on proteomic mass patterns from chemically treated whole-cell analyses. Biomarkers of the low molecular weight proteome in the MALDI-TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Given the atypical symptoms of brucellosis, it is difficult for clinicians to distinguish a group of diseases with similar symptoms. Although in recent years Hamidi et al [ 11 ] and Kazemi et al [ 12 ] showed that the discovery of some potential markers can play an effective role in the rapid diagnosis of brucellosis. However, at present, these methods are rarely actually used in clinical practice, especially in non-endemic areas of brucellosis.…”
Section: Introductionmentioning
confidence: 99%
“…Given the atypical symptoms of brucellosis, it is difficult for clinicians to distinguish a group of diseases with similar symptoms. Although in recent years Hamidi et al [ 11 ] and Kazemi et al [ 12 ] showed that the discovery of some potential markers can play an effective role in the rapid diagnosis of brucellosis. However, at present, these methods are rarely actually used in clinical practice, especially in non-endemic areas of brucellosis.…”
Section: Introductionmentioning
confidence: 99%
“…The first was Clover MSDAS, a commercial ad hoc software developed by Clover Bioanalytical Software (Granada, Spain, https://cloverbiosoft.com) for pre-processing of the protein spectra, biomarker detection and automatic typing with well-known ML algorithms: Random Forest (RF), K-Nearest Neighbor (KNN), Partial Least Squares Discriminant Analysis (PLS-DA), Support Vector Machine (SVM), and Light Gradient Boosting Machine (Light-GBM). In Clover MSDAS, all algorithms underwent training using biomarkers identified by the software, as described in previous studies (Hamidi, Bagheri Nejad et al 2022; Busby, Doyle et al 2023; Candela, Arroyo et al 2023). The use of these biomarkers for differentiation of specific categories is referred to as Expert-Knowledge (EK).…”
Section: Methodsmentioning
confidence: 99%
“…In Clover MSDAS, all algorithms underwent training using biomarkers identified by the software, as described in previous studies (Hamidi, Bagheri Nejad et al 2022;Busby, Doyle et al 2023;Candela, Arroyo et al 2023). The use of these biomarkers for differentiation of specific categories is referred to as Expert-Knowledge (EK (auto, sqrt, log2).…”
Section: Automatic ML Bacteria Typingmentioning
confidence: 99%
“…78 It can be achieved by pretreatment of the specimens using strategies like differential centrifugation, affinity capture, magnetic precipitation, microchip separation, in-situ extraction, chromatography, and so on. [79][80][81][82][83] A large number of patient specimens are also required to establish reliable machine learning classifiers with sufficient enough learning data.…”
Section: Biomarker Discoverymentioning
confidence: 99%
“…The success of such a biomarker discovery methodology relies heavily on the samples pretreatment procedures to obtain as many mass peaks as possible, especially the peaks from low‐abundant proteins and peptides 78 . It can be achieved by pretreatment of the specimens using strategies like differential centrifugation, affinity capture, magnetic precipitation, microchip separation, in‐situ extraction, chromatography, and so on 79–83 . A large number of patient specimens are also required to establish reliable machine learning classifiers with sufficient enough learning data.…”
Section: Applications In Rapid Precise Diagnosticsmentioning
confidence: 99%